LAMA4-Regulating miR-4274 and Its Host Gene SORCS2 Play a Role in IGFBP6-Dependent Effects on Phenotype of Basal-Like Breast Cancer - Shkurnikov, Maxim; Nikulin, Sergey; Nersisyan, Stepan; Poloznikov, Andrey; Zaidi, Shan; Baranova, Ancha; Schumacher, Udo; Wicklein, Daniel; Tonevitsky, Alexander (Frontiers in Molecular Biosciences, 2019)
Specificity of RNAi to selected target is challenged by commonly reported either canonical or non-canonical off-target effects. Notably, more than half of all human microRNAs are co-expressed the protein–coding genes. Here we dissect regulatory subnetwork centered on IGFBP6 gene, which is associated with low proliferative state and high migratory activity of basal-like breast cancer. We inhibited expression of IGFBP6 gene in a model cell line for basal-like breast carcinoma MDA-MB-231, then traced secondary and tertiary effects of this knockdown to LAMA4, a laminin encoding gene that contributes to phenotype of triple-negative breast cancer. LAMA4-regulating miRNA miR-4274 and its host gene SORCS2 were highlighted as intermediate regulators of the expression levels of LAMA4, which correlated in a basal-like breast carcinoma sample subset of TCGA to the levels of SORCS2 negatively. Overall, our study points that the secondary and tertiary layers of regulatory interactions are certainly underappreciated. As these types of molecular event may significantly contribute to the formation of the cell phenotypes after RNA interference based knockdowns, further studies of multilayered molecular networks are warranted.